Self-monitoring urinary salt excretion device can be used for controlling hypertension for developing countries - Yasmin Jahan (Clinical Hypertension, 2019)
Abstract Restriction of dietary salt is widely recommended in the management of hypertension, but assessment of individual salt intake has drawn little attention. Monitoring nutritional salt intake through sodium excretion has been popular, because the main route for sodium (Na) excretion is through the urine. Nonetheless, direct measurement of dietary salt intake is time consuming and lacks accuracy. To collect a 24-h urine and measure the content is difficult method for most patients. In this review paper, we would like to explore the usefulness of measuring urinary salt excretion by using a self-monitoring device at home. Measuring daily overnight urine by the self-monitoring device at home will be useful for the management of hypertension suitable for each individual. From the recent increase of processed foods, the term “salt intake” would not accurately be equal to “sodium intake”. Devices measuring urinary sodium excretion have been developed and evaluated on their accuracy and correlation with sodium intake. They must be handy, simple and capable of measuring large populations to be useful for monitoring of daily salt intake and to guide salt restriction as well as the long-term effects by dietary salt intake.